Solar-driven CO2 reduction using modified earth-abundant ilmenite catalysts - Luévano Hipólito, E.; Fabela Cedillo, Mayte G.; Torres Martínez, Leticia M.; Zarazúa Morín, María Elvira (Elsevier, 2023)
Photocatalytic CO2 reduction is an alternative technology to the depletion of highly pollutant fossil fuels through the generation of renewable solar-based fuels. This technology requires that the photocatalysts be obtained directly from nature to scale up the process. Taking that into consideration, this work proposed the fabrication of sodium iron titanate (NaFeTiO4) photocatalysts from earth-abundant ilmenite mineral. The photocatalysts exhibited full spectrum light response, good electron transfer due to its unique tunnel structure that favored the formation of rod-like morphology. These properties promoted the solar-driven CO2 reduction to generate formic acid (HCOOH) with high selectivity (157 μmol g− 1 h− 1 ). It was found that higher synthesis temperatures promoted the formation of Fe3+ species, which decreased the efficiency for CO2 reduction. Also, the possibility of reduced the CO2 molecules in the air was studied with the NaFeTiO4 samples, which resulted in an efficiency of up to 93 μmol g− 1 h− 1 of HCOOH under visible light. The stability of the solar-driven CO2 reduction with the NaFeTiO4 photocatalysts was confirmed after seven days of continuous evaluation.